(3Yde JObjb GdMSGHGJ (B:s (3GdYdej (B/s - (3eMehO, QGaJ SdGeIs; (3RQjbGJ, YeQ eMeO s; (3cdHhfI, GMeO jhSa s ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2011)
(3eaghe h JYQja GdJObjb , CgOGag h CgejJg , JMOjO MLe GNJjGQGJ JObjb GdMSGHGJ h GSJNOGe GdeYGjfI GdGMUGFjI aj gPG GdeLGd , JObjb bGFeI GdeQcR GdeGdj , ebOeI dGSJNOGe CSGdjH GdJObjb HeSGYOI GdMGSH GdBdj h CSGdjH GdQbGHI Ydi GNJjGQ fXGe fYdheGJ GdGOGQI , JMdjd GdJhGab Hjf GdeYdheGJ GdeGdjI h GdeYdheGJ GdeJYdbh HgG HhGSWI GdJMdjd GdehVhYj HeG aj Pdc GdGLQGAGJ GdJMdjdjI , eYGjjQ JObjb GdMSGHGJ h GdbhGYO GdYGeI dgG , GdQbGHI , GdJObjb GdGOGQj h GdJObjb GdGLJeGYjs
(3eUWdMGJ U(B.269s
Keywords: (3GdeMGSHIs; (3eQGLYI GdMSGHGJs